2004
DOI: 10.1007/s00122-004-1808-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity associated with variation in silage corn digestibility for three O-methyltransferase genes involved in lignin biosynthesis

Abstract: Polymorphisms within three candidate genes for lignin biosynthesis were investigated to identify alleles useful for the improvement of maize digestibility. The allelic diversity of two caffeoyl-CoA 3-O-methyltransferase genes, CCoAOMT2 and CCoAOMT1, as well as that of the aldehyde O-methyltransferase gene, AldOMT, was evaluated for 34 maize lines chosen for their varying degrees of cell wall digestibility. Frequency of nucleotide changes averaged one SNP every 35 bp. Ninety-one indels were identified in non-co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
52
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 45 publications
1
52
1
Order By: Relevance
“…These findings suggest that the presence of multiple introns plays an important role in the acquisition of gene function, such as the incorporation of new functional domains; these introns are gradually lost during evolution. Studies of COMT genes in different species have indicated that the size and number of introns varies considerably among species (Besse et al 2009, Bout and Vermerris 2003, Guillet-Claude et al 2004. The CAD gene has lost introns during the evolutionary process, so we speculate that the presence of these introns in ancestral species was essential for the CAD gene to acquire new functional properties.…”
Section: Discussionmentioning
confidence: 78%
“…These findings suggest that the presence of multiple introns plays an important role in the acquisition of gene function, such as the incorporation of new functional domains; these introns are gradually lost during evolution. Studies of COMT genes in different species have indicated that the size and number of introns varies considerably among species (Besse et al 2009, Bout and Vermerris 2003, Guillet-Claude et al 2004. The CAD gene has lost introns during the evolutionary process, so we speculate that the presence of these introns in ancestral species was essential for the CAD gene to acquire new functional properties.…”
Section: Discussionmentioning
confidence: 78%
“…1b and 1c), which was in concordance with the maize and Eragrostis curvula CCoAOMT1 gene intron-exon arrangement. In contrast, three introns were identified in rice CCoAOMT and maize CCoAOMT2 (Guillet-Claude et al, 2004).…”
Section: Isolation Of Csccoaomt Genementioning
confidence: 86%
“…1, also see [29]) indicating that cell-wall composition and possibly architecture were altered due to selection. Cell-wall composition is a complex trait controlled through the actions of many genes [34][35][36][37], and it is likely that genotypes with altered lignin and DMD could arise from several different combinations of genes. Furthermore, lignin is a mixed polymer, composed of different aromatic compounds cross-linked to each other and to cell-wall carbohydrates [36][37][38][39].…”
Section: Discussionmentioning
confidence: 99%